2015
DOI: 10.1074/jbc.m115.695189
|View full text |Cite
|
Sign up to set email alerts
|

The T210M Substitution in the HLA-a*02:01 gp100 Epitope Strongly Affects Overall Proteasomal Cleavage Site Usage and Antigen Processing

Abstract: MHC class I-restricted epitopes, which carry a tumor-specific mutation resulting in improved MHC binding affinity, are preferred T cell receptor targets in innovative adoptive T cell therapies. However, T cell therapy requires efficient generation of the selected epitope. How such mutations may affect proteasome-mediated antigen processing has so far not been studied. Therefore, we analyzed by in vitro experiments the effect on antigen processing and recognition of a T210M exchange, which previously had been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…As already anticipated, 20S proteasomes obtained from melanoma cell lines did not produce the minimal gp100 209‐217 epitope in detectable amounts, confirming the result of previous studies carried out with various proteasomes and conditions . Two N‐extended versions – i.e .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…As already anticipated, 20S proteasomes obtained from melanoma cell lines did not produce the minimal gp100 209‐217 epitope in detectable amounts, confirming the result of previous studies carried out with various proteasomes and conditions . Two N‐extended versions – i.e .…”
Section: Resultssupporting
confidence: 88%
“…Proteasomes were purified from cell lines grown in the absence of inflammatory stimuli to analyze their baseline activity. Consistently with previous studies [10,12,13,35], the minimal gp100 209-217 epitope was not detectable in melanoma proteasome digestions, whereas its N-terminal extended versions could be quantified ( Fig. 2A).…”
Section: Cleavage Preferences Of Proteasome Subtypes Expressed In Humsupporting
confidence: 92%
See 2 more Smart Citations
“…The few pioneering studies on PCPS had already provided hints about generative 6 mechanisms. For instance, they suggested that PCPS prefers specific peptide sequences, although the limited number of spliced peptides/epitopes identified has so far precluded an analysis with sufficient statistical power (2,8,(14)(15)(16)(17)(18)(19)(20)(21). With our large pool of spliced antigenic peptides this became possible.…”
mentioning
confidence: 99%